(3GdZjK GdefSLe aj TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s; (3eDjO GdOjf CHj ESeGYjd GdMSjf Hf Ydj aNQ GdcJGH GdYejO GdWZQGFj,J (B514 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOQ ef JCOH , hQaY bOQ ef JCgd ddYde hJCgH , hLed ef JOQY dHGS GdaVd hJOQH s
(3BNQgG (B:s
(3hZRGd ZRG aDGOi HSge hSfGf ef WQag GdhSfGf ce SbGfi ef KZQg cCS NeQ aQTaJ GdSdGa ef CbMhGf hgPG BNQ GdLRA GdChd , hgh GdfUa ef TQM dGejI GdYLe jJdhg GdLRAGdKGfi hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1213s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs